2009
DOI: 10.1200/jco.2008.17.3930
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor Mutations in Plasma DNA Samples Predict Tumor Response in Chinese Patients With Stages IIIB to IV Non–Small-Cell Lung Cancer

Abstract: EGFR mutations can be reliably detected in plasma DNA of patients with stages IIIB to IV NSCLC and can be used as a biomarker to predict tumor response to TKIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
251
6
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 243 publications
(269 citation statements)
references
References 20 publications
11
251
6
1
Order By: Relevance
“…Nevertheless, it's difficult to obtain tumor tissues from patients with advanced or recurrent NSCLC. Although several studies have focused on exploring the potential possibility of detecting EGFR mutation in circulating tumor DNA from plasma or other non-tissue samples, the concordance rate of EGFR mutation status between these samples and matched tumor tissue were not stable, varying from 59.1% to 92% [33][34][35][36]. It seems that assessing EGFR mutation status using blood sample is not absolutely accurate.…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, it's difficult to obtain tumor tissues from patients with advanced or recurrent NSCLC. Although several studies have focused on exploring the potential possibility of detecting EGFR mutation in circulating tumor DNA from plasma or other non-tissue samples, the concordance rate of EGFR mutation status between these samples and matched tumor tissue were not stable, varying from 59.1% to 92% [33][34][35][36]. It seems that assessing EGFR mutation status using blood sample is not absolutely accurate.…”
Section: Discussionmentioning
confidence: 97%
“…In the study of Bay et al, 109 consisting of 77 patients with primary tumor EGFR mutations, 63 reported identical alterations in the matched plasma. Moreover, 7% of patients with plasma mutations had no detectable alterations in the corresponding primary tumors and, similarly, 6% of patients with tumor mutations had no detectable EGFR alterations in the corresponding plasma.…”
Section: Biological Samples Suitable For Molecular Characterizationmentioning
confidence: 98%
“…105 Subsequent studies have attempted to confirm these results in larger case series. [106][107][108][109][110][111][112] Indeed, using a range of different methodologies, serum/plasma EGFR mutations have been reported in over 70% of patients in which the tumor tissue showed the same mutation (Table 2).…”
Section: Biological Samples Suitable For Molecular Characterizationmentioning
confidence: 99%
“…In lung SqCCs, EGFR mutations are considered as a rare molecular event; they are reported in less than 5% of Caucasians and are reported at seemingly higher rates in Asians, ranging from 0% to 20.3% (10,14,(24)(25)(26)(27)(28)(29)(30). In our study, the frequency of EGFR mutation in advanced lung SqCC patients was 9.6%.…”
Section: Discussionmentioning
confidence: 99%